Heterogeneity of rDNA distribution and genome size in Silene spp - Siroký, J; Lysák, M A; Dolezel, J; Kejnovský, E; Vyskot, B (Chromosome research, 2001)
Genus Silene L. (Caryophyllaceae) contains about 700 species divided into 44 sections. According to recent taxonomic classification this genus also includes taxa previously classified in genera Lychnis and Melandrium. In this work, four Silene species belonging to different sections were studied: S. latifolia (syn. Melandrium album, Section Elisanthe), S. vulgaris (Inflatae), S. pendula (Erectorefractae), and S. chalcedonica (syn. Lychnis chalcedonica, Lychnidiformes). Flow cytometric analysis revealed a genome size of 2.25 and 2.35 pg/2C for S. vulgaris and S. pendula and of 5.73 and 6.59 pg/2C for S. latifolia and S. chalcedonica. All four species have the same chromosome number including the pair of sex chromosomes of the dioecious S. latifolia (2n = 2x = 24). Double target fluorescence in-situ hybridization revealed the chromosomal locations of 25S rDNA and 5S rDNA. A marked variation in number and localization of rDNA loci but no correlation between the numbers of rDNA clusters and genome size was found. FISH and genome size data indicate that nuclear genomes of Silene species are highly diversified as a result of numerous DNA amplifications and translocations.
Keywords: Flow Cytometry; Models, Genetic; buněčné jádro; modely genetické; Silene; Cell Nucleus; buněčné jadérko; průtoková cytometrie; Cell Nucleolus; chromozomy; DNA, Ribosomal; hybridizace in situ fluorescenční; In Situ Hybridization; Chromosomes; ribozomální DNA; In Situ Hybridization, Fluorescence; hybridizace in situ